Planning arrangement of medley regional songs on choir for the preservation of local culture - Suryati, Suryati (Linguistics and Culture Review, 2021)
This study aims to motivate students' creativity in making musical compositions in Cultural Arts and Fine Arts learning. Student creativity is needed to preserve cultural arts. This study focuses on making folk song medley arrangements and their implementation for high school choirs. This study uses a qualitative descriptive method. Data was obtained through literature study, observation, and field studies. The sample of this research is the student choir group at SMA Muhammadiyah 2 Yogyakarta. Data were analyzed using the Miles and Huberman models, namely by data reduction, tabulation, presentation, and conclusion. The results showed that the arrangement of a medley of folk songs could make students more enthusiastic and creative in learning Arts, Culture, and Arts, especially music. In addition, it was also shown that students were more creative in expressing their musical performances through the choir. The songs that were successfully arranged were “Gundul-Gundul Pacul”, “Cublak-Cublak Suweng” and “Padang Bulan”.